ANALYSIS OF SILENT READING BOOK CLUB’S ROLE IN DEVELOPING COMMUNITY READING INTEREST AND LITERACY - Millenia, Dian; Nurhayati, Sri; Ansori, Ansori (Universitas Riau Kepulauan, 2025)
Studi ini meneliti Silent Reading Book Club